1992
DOI: 10.1111/j.1471-4159.1992.tb11014.x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Arachidonic Acid and Diacylglycerol Second Messengers from Polyphosphoinositides in Ischemic Fetal Brain

Abstract: Intracerebral administration of [3H]arachidonic acid ([3H]ArA) into 19-20-day-old rat embryos, resulted in a rapid incorporation of label into brain lipids. One hour after injection, 55.6 +/- 8.2, 18.0 +/- 3.4, and 13.7 +/- 1.3% of the total radioactivity was associated with phosphatidylcholine, phosphatidylinositol, and phosphatidylethanolamine, respectively. Approximately 10% of radioactivity was found acylated in neutral lipids of which free ArA comprised only 1.5 +/- 0.2% of the total radioactivity. Comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…20-hydroxyeicosatetraenoic acid; middle cerebral artery occlusion; cytochrome P-450A; N-hydroxy-N'-(4-butyl-2-methylphenyl)-formamidine HYPERTENSION IS A MAJOR RISK factor for stroke, but the factors that contribute to the increased incidence and severity of ischemic stroke in hypertension remain to be determined (46). Previous studies have indicated that arachidonic acid (AA) is released into cerebrospinal fluid following cerebral ischemia (1,31,42,56). AA is converted by cytochrome P-450 (CYP) enzymes in cerebral arteries to a potent vasoconstrictor, 20-hydroxyeicosatetraenoic acid (20-HETE) (15,16,32).…”
mentioning
confidence: 99%
“…20-hydroxyeicosatetraenoic acid; middle cerebral artery occlusion; cytochrome P-450A; N-hydroxy-N'-(4-butyl-2-methylphenyl)-formamidine HYPERTENSION IS A MAJOR RISK factor for stroke, but the factors that contribute to the increased incidence and severity of ischemic stroke in hypertension remain to be determined (46). Previous studies have indicated that arachidonic acid (AA) is released into cerebrospinal fluid following cerebral ischemia (1,31,42,56). AA is converted by cytochrome P-450 (CYP) enzymes in cerebral arteries to a potent vasoconstrictor, 20-hydroxyeicosatetraenoic acid (20-HETE) (15,16,32).…”
mentioning
confidence: 99%
“…As described, prominent changes in lipids are reportedly accompanied in the ischemic brain, where a rapid decrease in phosphatidylinositol-4,5-bisphosphate (PIP 2 ) levels together with a parallel accumulation of diacylglycerol (DG) is observed (Kunievsky et al 1992). In addition, levels of PIP, PIP 2 , and DG approach plateau values after 10 min of ischemia ), a 30 min recirculation period after 15 min of ischemia engenders increases in PIP and PIP 2 , whereas levels of DG decrease promptly toward control values (Moto et al 1991;Yoshida et al 1986).…”
Section: Discussionmentioning
confidence: 95%
“…Glutamate excitotoxicity causes a massive inXux of Ca 2+ that activates various catabolic processes, culminating in neuronal cell death (Choi 1985(Choi , 1995Lau and Tymianski 2010). Furthermore, previous reports show that prominent changes in lipids are accompanied in the ischemic brain, in which a rapid decrease in phosphatidylinositol-4,5-bisphosphate (PIP2) levels together with a parallel accumulation of diacylglycerol (DG) occurs (Kunievsky et al 1992). These Wndings suggest that phosphoinositide (PI) pathway is involved in this process.…”
Section: Introductionmentioning
confidence: 95%
“…Intrauterine ischemia leads to rapid translocation of PKC from the cytosol to the membrane fraction followed by loss in the content and activity of the enzyme (Louis et al, 1988). Polyphosphoinositides are hydrolyzed by a phospholipase C with formation of diacylglycerol at the beginning of ischemic insult followed by a phospholipase A 2 mediated liberation of arachidonic acid as 8 Savithiry and Kumar ischemia progresses (Kunievsky et al, 1992). It appears that the release of arachidonic acid from polyphosphoinositides could be part of a signal transduction chain responsible for PKC activation (Kunievsky et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Polyphosphoinositides are hydrolyzed by a phospholipase C with formation of diacylglycerol at the beginning of ischemic insult followed by a phospholipase A 2 mediated liberation of arachidonic acid as 8 Savithiry and Kumar ischemia progresses (Kunievsky et al, 1992). It appears that the release of arachidonic acid from polyphosphoinositides could be part of a signal transduction chain responsible for PKC activation (Kunievsky et al, 1992). Gangliosides administered prior to the ischemic episode prevent downregulation of PKC in ischemic fetal rat brain (Magal et al, 1990).…”
Section: Discussionmentioning
confidence: 99%